Mandibular osteomyelitis after traumatic tooth extraction: Case report (Research, Society and Development, 2022)
The objective of this study is to report a case of chronic osteomyelitis in the unilateral body, branch and head of the jaw after traumatic extraction. Male patient, 45 years old, referred to the Oral-Maxillofacial Surgery and Traumatology Service of Maria Aparecida Pedrossian’s University Hospital in Campo Grande - MS for the treatment of odontogenic infection affecting the pre-auricular region with right oral and submandibular extension, hardened on palpation and with extraoral fistula with active drainage of purulent secretion. On intraoral examination, alveoli with signs of recent extraction, teeth 47 and 48, and limitation of mouth opening. On tomography, bone degeneration of the head and right mandibular branch compatible with osteomyelitis. Intraoral and extraoral drainage was performed with debridement of the alveolar region of teeth 47 and 48 and installation of a transfixing drain under local anesthesia. On biochemical examinations, he presented iron deficiency anemia, with reduced hemoglobin values, suggestive of low immune response leading to rapid spread of infection. Patient remained hospitalized for intravenous drug treatment for 59 days (vancomycin, ciprofloxacin and meropenem) for remission of the infectious condition associated with culture procedures, antibiogram and curettage of the mandibular body region. After the mentioned treatment, the patient presented a satisfactory response with remission of symptoms and continued in outpatient follow-up without complaints and/or complications.